Connecting Sustainable Development and Corporate Sustainability through a 2030 Agenda Disclosure Index: Evidence from the Top-listed Iberian Companies - Suárez-Serrano, Eugenia; González-Torre, Pilar L.; Covián-Regales, Enrique (European Journal of Sustainable Development, 2025)
To conciliate theories regarding the connection between corporate sustainability and sustainable development, this study presents a 2030 Agenda Disclosure Index compatible with different perspectives and standards, and which is tested in the contents of the sustainability reports of the top listed Iberian companies. Unlike studies that construct the SDG contribution variable as a dummy, reflecting only